Comparison of alkyl xanthates degradation in aqueous solution by the O3 and UV/O3 processes: Efficiency, mineralization and ozone utilization. (1st October 2015) - Fu, Pingfeng; Feng, Jie; Yang, Tianwen; Yang, Huifen
Graphical abstract: Highlights: The UV/O3 achieves higher ratio of xanthate mineralization and ozone utilization. Xanthates' –CSS − groups were significantly mineralized to form SO4 2− ions. Direct oxidation of xanthates with O3 is predominant in O3 process. Hydroxyl radicals promote mineralization of xanthates by photolysis of O3 . Abstract: The removal of four alkyl xanthates (ethyl, isopropyl, n -butyl and n -amyl) by the O3 and UV/O3 processes was investigated in a semi-batch, bubble column reactor. Each alkyl xanthate was almost completely decomposed within 10 min by both the O3 and UV/O3 processes, confirmed by UV–vis spectroscopic analysis. However, the mineralization of xanthates was less effective compared to simple decomposition of xanthate molecules. The removal of COD in 40 min was just 50.9–61.2% by O3 oxidation of four alkyl xanthates, but the removal increased to 66.2–81.2% by the UV/O3 process. Additionally, the ozone utilization ratio increased by 15–30% by adding UV radiation in the O3 process. The sulfur mineralization ratio of –CSS − groups of xanthates in 40 min reached approximately 45% and 55% in the O3 and UV/O3 processes, respectively, revealing the effective mineralization of sulfur byproducts such as CS2, COS and S 2− . The enhancement mechanism of xanthate mineralization and ozone utilization was discussed for the UV/O3 system. In a weak acid solution, direct oxidation with O3 was predominant for O3 process. In contrast, O3 could be readily decomposed by UV radiation to form reactive radicals in the UV/O3 process, thus enhancing xanthate mineralization and ozone utilization. Compared to the O3 process, the UV/O3 process was more effective in mineralization of xanthates and reduced O3 consumption.